2000
DOI: 10.1016/s0893-133x(00)00099-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Repetitive Transcranial Magnetic Stimulation Increases the Expression of Brain-Derived Neurotrophic Factor and Cholecystokinin mRNA, but not Neuropeptide Tyrosine mRNA in Specific Areas of Rat Brain

Abstract: Repetitive transcranial magnetic stimulation (rTMS) is increasingly used as a therapeutic tool in various neurological and psychiatric disorders, and we recently found that it has a neuroprotective effect both in vitro andTranscranial magnetic stimulation (TMS), a technique in which a time-varying strong electric current is applied through a coil held in direct contact with the subject's head, was originally developed for diagnostic use in neurology (for review see Rossini and Rossi 1998). A possible effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
109
1
12

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 255 publications
(129 citation statements)
references
References 63 publications
7
109
1
12
Order By: Relevance
“…Therefore, the current data could be extrapolated to the clinical condition and provide new insights into the mechanisms underlying the antidepressant effects of rTMS. With respect to the changes in HPA system activity, the present findings further support the concept of a common final pathway for different types of antidepressant treatment strategies (e.g., Müller et al 2000).…”
Section: Rtms: Differential Effects On Anxiety-related Behavior and Csupporting
confidence: 79%
See 4 more Smart Citations
“…Therefore, the current data could be extrapolated to the clinical condition and provide new insights into the mechanisms underlying the antidepressant effects of rTMS. With respect to the changes in HPA system activity, the present findings further support the concept of a common final pathway for different types of antidepressant treatment strategies (e.g., Müller et al 2000).…”
Section: Rtms: Differential Effects On Anxiety-related Behavior and Csupporting
confidence: 79%
“…Moreover, we recently demonstrated that long-term rTMS in rats has a neuroprotective effect both in vitro and in vivo (Post et al 1999). In addition, we observed rTMS-induced changes in the expression of brain-derived neurotrophic factor (BDNF) and cholecystokinin simi-lar to those reported after antidepressant drug treatment and electroconvulsive seizures (Müller et al 2000). These data suggest that a common molecular mechanism may underlie different antidepressant treatment strategies and that animal experiments might be helpful in understanding the neurobiological changes induced by rTMS, which still remain to be investigated.…”
supporting
confidence: 52%
See 3 more Smart Citations